Women’s Perceptions Towards Climate Variability: A Case of Female Farmers in Bundelkhand Region of Uttar Pradesh, India - , Deepali Suryawanshi; , Bijaya Laxmi Sahu; , Mahima Sharma; , Gaurav Chaudhri; , Eshant Kumar Sukdeve; , Jyoti Dudi; , Anjali Pandey; , Somdutt Tripathi (Archives of Current Research International, 2025)
The study was conducted with the aim of women perception towards climate change in Bundelkhand region of Uttar Pradesh. Based on the output of this study, the sample had consisted of women aged 26–35 years (36.25%), the majority of whom were married (88.75%), belonged to medium-sized families (46.25%), and had a moderate monthly income (53.75%). Most participants had limited exposure to mass media (61.25%) and owned small landholdings (1–2 hectares) (65%), with 42.50%. A majority of women had experienced noticeable climate change effects, including rising temperatures, unpredictable weather patterns, reduced groundwater availability, altered plant nutrient content, delayed rainfall, increased drought frequency, and soil erosion. Most respondents agree on the environmental and economic effects of climate change. Data were analyzed using correlation coefficient which revealed that family Size, annual income, farming experience, and marital status were strongly and significantly associated with perceptions of climate change (p < 0.001). Age, Education, and Mass Media Exposure also showed statistically significant with moderate correlations (p < 0.05).